(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides a scientific and philosophical comparative analysis of the moral and aesthetic views of Muslim Eastern and Western philosophers. It is well known that while Eastern aesthetics is characterized by intellectual potential and moral beauty, it has been considered by some modern Western theorists to be a legacy of antiquity and has reached the abyss of "absurd aesthetics" within its fictional light cultures. In this context, the article examines the teachings of the Western classical philosopher Immanuel Kant, which have an inherently unique and rich spiritual substrate, and makes a comparative analysis with the concept of fine morality that forms the basis of Islam. In other words, it examines the scientific heritage of the geniuses of medieval Muslim Eastern and Western civilization, approaches the development of the national cultural heritage in terms of the urgency of an in-depth study of its place and role in the history of mankind and modern civilization.